2008
DOI: 10.1093/eurheartj/ehn249
|View full text |Cite
|
Sign up to set email alerts
|

The potential clinical utility of intravascular ultrasound guidance in patients undergoing percutaneous coronary intervention with drug-eluting stents

Abstract: IVUS guidance during DES implantation has the potential to influence treatment strategy and reduce both DES thrombosis and the need for repeat revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(104 citation statements)
references
References 22 publications
5
93
4
1
Order By: Relevance
“…2,6,7 Previous studies with bare metal stent and DES have shown that IVUS guidance during percutaneous coronary intervention (PCI) improved clinical outcomes. 8,9 However, the impact of IVUS on clinical outcomes has been controversial according to different lesion subsets. [10][11][12] Long-term clinical benefits of IVUS guidance during PCI at bifurcation lesions are especially uncertain and need further investigation.…”
mentioning
confidence: 99%
“…2,6,7 Previous studies with bare metal stent and DES have shown that IVUS guidance during percutaneous coronary intervention (PCI) improved clinical outcomes. 8,9 However, the impact of IVUS on clinical outcomes has been controversial according to different lesion subsets. [10][11][12] Long-term clinical benefits of IVUS guidance during PCI at bifurcation lesions are especially uncertain and need further investigation.…”
mentioning
confidence: 99%
“…However, they could not explain the precise mechanism of the late mortality benefit of using IVUS-guided PCI. Roy, et al 23) proposed that using IVUS guidance may improve the long-term survival rate by reducing the risk of stent thrombosis in DES treatment. Park,et al 18) mentioned that the superior benefit of IVUS guidance in DES treatment was not consistently observed in the other Cox model using PS as a covariate for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 6,18,23,[26][27][28] did not have a primary focus on the clinical outcomes of non-complex LMCA disease treated with a single stenting technique. Only Agostoni, et al 22) reported that when ostial or mid-LMCA disease is treated with DES, the rate of cardiac events is particularly low.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IVUS is a useful tool for determining optimal DES implantation. Roy et al 23 reprted that the clinical outcomes of 884 patients undergoing IVUS-guided intracoronary DES TAKAYAMA T et al…”
Section: Ivus-guided Des Implantationmentioning
confidence: 99%